RELEVANSI MODEL PEMBELAJARAN KOLABORATIF DALAM PERSPEKTIF AL-QUR’AN DENGAN TUNTUTAN KERJASAMA DALAM TIM DI DUNIA KERJA - Nazila Mumtaza Zamhariroh; Ahmad Yusam Thobroni (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This article discusses the relevance of collaborative learning models from the perspective of the Qur’an in relation to the demands of teamwork in the workplace. The collaborative learning model, which emphasizes cooperation, communication, and shared responsibility, aligns with principles taught in the Qur'an, such as ta'awun (mutual assistance in goodness) and musyawarah (collective decision-making). Using a qualitative-descriptive approach, this study conducts a literature review to identify the alignment between collaborative learning principles and the teamwork skills increasingly needed in today’s workplace. The findings indicate that implementing collaborative learning not only aids in academic skill development but also equips students with essential interpersonal skills for work environments, such as effective communication, conflict management, and problem-solving. In conclusion, integrating Qur'anic values into collaborative learning can strengthen students' character and social skills, thus better preparing them to meet the demands of teamwork in professional settings.